PENGEMBANGAN TES DIAGNOSTIK TWO TIER MENGGUNAKAN APLIKASI GOOGLE FORM PADA MATERI TEKANAN DI SMP - Putri, Agus Setyawati; Silitonga, Haratua Tiur Maria; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to develop a two-tier diagnostic test using the google form application on pressure materials in junior high schools. Research on the development of a two-tier diagnostic test using the google form application on this pressure material uses research and development (RD) methods. This research was carried out in two stages of trial, namely product trials which were carried out at SMP Negeri 1 Sungai Raya and trial usage at SMP Negeri 1 and 9 Sungai Raya. The instrument used is a two-tier diagnostic test which is distributed using the google form application. This study presents 21 items on the diagnostic test divided into two categories moderate and easy. There are 11 questions while the easy questions have 10 questions. The content validity level of this study was 0.74. Then the reliability shows 0.804 in product trials and 0.711 in usage trials. With a readability level of 4.42, it is categorized as usable in junior high school. Based on the results of panel validation regarding the use of google forms with the Aiken 1 index and some student response data, the google form application is in the high category (77.33%). So that the google form application can be used for diagnostic test questions.Keywords: Development, Diagnostic Test, Google Form, Identification, Pressure, Two Tier